Structure–charge relationship – the case of hematite (001). (30th April 2015) - Lützenkirchen, Johannes; Heberling, Frank; Supljika, Filip; Preocanin, Tajana; Kallay, Nikola; Johann, Florian; Weisser, Ludger; Eng, Peter J.
Abstract : We present a multidisciplinary study on the hematite (001)–aqueous solution interface, in particular the relationship between surface structure (studied via surface diffraction in a humid atmosphere) and the macroscopic charging (studied via surface- and zeta-potential measurements in electrolyte solutions as a function of pH). Upon aging in water changes in the surface structure are observed, that are accompanied by drastic changes in the zeta-potential. Surprisingly the surface potential is not accordingly affected. We interpret our results by increasing hydration of the surface with time and enhanced reactivity of singly-coordinated hydroxyl groups that cause the isoelectric point of the surface to shift to values that are reminiscent of those typically reported for hematite particles. In its initial stages after preparation the hematite surface is very flat and only weakly hydrated. Our model links the entailing weak water structure with the observed low isoelectric point reminiscent of hydrophobic surfaces. The absence of an aging effect on the surface potential vs. pH curves is interpreted as domination of the surface potential by the doubly coordinated hydroxyls, which are present on both surfaces.